The Psychological Impact of The Information Environment on the Consciousness of Young People: Problems and Solutions (Eurasian Journal of Learning and Academic Teaching, 2023)
The paper deals with the issues of information environment and its psychological impact on the consciousness and behavior of young people, as well as provides methods of psychological manipulation and highlights the forms of information-psychological defense of personality.